Homemade modelling clay as a tool to introduce a critical thinking point of view - Estradas, Ana (2022)
This work intends to reflect, from the proposal of homemade modelling clay manufacture, what questions can (future) teachers take into account when planning an activity. Modelling clay is a very plastic substance that sometimes has toxic materials for children and / or the environment in its composition. A good alternative for the teacher is to do himself/herself the modelling clay for and with children using non-toxic, natural, local, low-cost ingredients. Since planning is an important part of the teacher's work, issues such as Ethics, Costs, Environment, Health and Safety should not be ignored. But how much are these aspects considered, introduced, debated and taken into account? To understand what importance is given to all these aspects a two hours session was developed in a class of Elementary and Early Education Bachelor’s Degree. The session included a) a presentation of the concepts through the Mentimeter platform followed by a debate and b) the experimentation of practical proposals presented as a possible solution to the identified problems. At the end c) an individual questionnaire was passed to assess the relevance of the questions and/or generate other questions/suggestions to be discussed and also to obtain a synoptic evaluation of the session. The result of the developed activity shows that in educational activities, the pedagogical issues of child development are much studied and debated and are highly valued in teachers' plans. However, issues such as ethics, the relationship that specific activity may have with the community or environment, and the good use / creation of resources are often ignored. To bring this “secondary issues” to the agenda it is not only necessary; it is a challenge!